Does Regular Lipid Apheresis in Patients With Isolated Elevated Lipoprotein(a) Levels Reduce the Incidence of Cardiovascular Events?. Issue 2 (25th July 2013) - Rosada, Adrian; Kassner, Ursula; Vogt, Anja; Willhauck, Michael; Parhofer, Klaus; Steinhagen‐Thiessen, Elisabeth
Abstract Elevated lipoprotein(a) (Lp(a)) is known as an independent risk factor for atherosclerosis and cardiovascular events. Regular lipid apheresis decreases elevated Lp(a) concentrations. However, there is a lack of reliable data regarding the effect of lipid apheresis on cardiovascular endpoints. To assess the effects of apheresis, we compared the occurrence of cardiovascular events in 37 patients treated regularly with lipid apheresis at the time periods of preinitiation of apheresis and during apheresis treatment. A retrospective analysis of 37 patients (35 men and two women; aged 58 years ± 11 [mean ± standard deviation]; body mass index 26 kg/m2 ± 3; low‐density lipoprotein (LDL)‐cholesterol before apheresis 84 mg/dL ± 21; Lp(a) before apheresis 112 mg/dL ± 34) treated regularly with lipid apheresis was performed. Patients' medical records were screened for cardiovascular events at the preapheresis and during apheresis periods. Apheresis led to a significant reduction of lipid levels (LDL cholesterol −60%; Lp(a) –68%) measured after apheresis. The event‐free survival rate after 1 year in the preapheresis period was 38% (22–54%, 95% confidence interval [CI]) vs. 75% (61–89%, 95% CI) in the during‐apheresis period with a statistically significant difference (P < 0.0001). Apheresis seems to lower the progression of atherosclerosis leading to a reduced number of cardiovascular events in hyperlipoproteinemia(a). Because prospective and controlled trials are lacking, the therapeutic effectiveness of lipid apheresis can only be estimated.